The Role of Zakat Community Development Program Institutions in Increasing Youth Creativity in Selat Village, West Lombok Regency - Rudi Siswandi; Ahmad Fauzan; Edy Kurniawansyah; Muh. Zubair (Abjadia, 2023)
This study aims to determine the role of Zakat Community Development program institutions, the creativity of Youth in Selat village, West Lombok district, and the role of Zakat Community Development program institutions in increasing youth creativity in Selat village, West Lombok district. The research method used is a qualitative approach with a survey type. The subject of this research is the head of the program or commonly called a friend of zakat at the Zakat Community Development program institution in Selat village, West Lombok district. Informants in this study were youth and the people of Selat village who had involvement with Zakat Community Development. The informants for this study were determined with certain considerations so that the data from the informants were not arbitrary or commonly referred to as a purposive sampling technique. Data collection was carried out by observation, interview and documentation techniques. Data analysis was carried out using the Miles and Huberman model which took place in four cycles, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the Zakat Community Development (ZCD) program institution has a very important role in increasing youth creativity in Selat village, West Lombok district, this can be seen from ZCD's commitment in facilitating financing, utilization of natural resources, training and coaching, can be seen also on creative products produced by youth.